Islamic economics and COVID-19 the economic, social and scientific consequences of a global pandemic - Choudhury, Masudul Alam 1948- (Routledge Focus on Economics and Finance, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Prelude -- Contents -- List of tables -- List of figures -- Acknowledgement -- Preface -- Prologue -- 1 The socio-scientific development outlook for global future -- 2 Pandemic treatments for transforming cell mutation into normalcy in unity of knowledge as the ontological premise of technical modelling -- 3 Wellbeing and sustainability: lessons from coronavirus episode in the light of Tawhidi unity of knowledge -- 4 Normalizing pandemic episode by science-economy-society moral inclusiveness -- 5 A generalized model of science-economy-society moral inclusiveness in complex pandemic regime -- 6 The role of educational reform in COVID-19 normalization -- 7 Selected reforms in business-pandemic studies to accord with the model of science-economy-society moral inclusiveness -- 8 Conclusion: future pandemic model beyond COVID-19 -- Index.